Therapeutic drug monitoring of imatinib in chronic myeloid leukemia: experience from 1216 patients at a centralized laboratory. (31st October 2012) - Bouchet, Stéphane; Titier, Karine; Moore, Nicholas; Lassalle, Régis; Ambrosino, Basmah; Poulette, Sylvie; Schuld, Peter; Belanger, Coralie; Mahon, François‐Xavier; Molimard, Mathieu
Abstract: This study set out to examine in a large real‐life cohort of patients with chronic myeloid leukemia (CML) the impact of imatinib threshold of 1000 ng/mL on molecular response, as suggested in a small subset of patients. Patient plasma samples were submitted from around France to a central facility, free of charge under the auspices of the European Treatment and Outcome Study (EUTOS) for CML. Submitting physicians were required to complete an 'imatinib monitoring request form', including details of why therapeutic drug monitoring (TDM) was requested, dose and duration of imatinib treatment, cytogenetic and molecular response, adverse events, and concurrent medications. Imatinib trough plasma concentration ( C min ) was measured at the central facility. Among 1985 eligible plasma samples analyzed, from 1216 CML patients, imatinib C min correlated positively with reported imatinib dose, but interpatient variability in C min was high (60%). A logistic regression analysis revealed that treatment duration and imatinib C min > 1000 ng/mL were significantly associated with major and complete molecular responses with odds ratios of 1.69 and 2.08, respectively. These data support in real‐life setting that imatinib C min threshold of 1000 ng/mL is associated with major and complete molecular response and that TDM could play an important role in dose optimization.